Evaluasi Usability Situs Web Sistem Informasi Perencanaan Pembangunan Daerah (SIPPD) v3.0 menggunakan Metode Usability Testing (Studi Kasus : Bappelitbangda Kota Batu) - Arinda Dewi Listikowati; Ismiarta Aknuranda; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Sistem Informasi Perencanaan Pembangunan Daerah (SIPPD) v3.0 is an information system that used by Bappelitbangda (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah) to support regional development planning activities. This information system was built to keep and ensure the achievement of integration, synchronization, and good synergy between government affairs. However, in its use there are indications of problems in understanding menu functions, different names on page titles and submenu links, system implementation that is still running 50%, and not all users understand the system. Based on the description above, it can be said that the problem is included in usability, so usability evaluation needs to be done using the usability testing method. The usability testing method is used to explore usability problems by testing the system on representative users and for measuring usability. Usability levels that measured are components of learnability, efficiency, errors, and satisfaction. To find out the level of satisfaction in accessing the system, it was measured by using the System Usability Scale (SUS) questionnaire. Then for the improvement of the interface design made by referring to the Human Health Service (HHS). Tests in this study were carried out twice, namely the initial test before repairs and further testing was carried out after being given recommendations for improvements in the form of a prototype. The results obtained from the calculation of usability level on further testing experienced an increase in the components of learnability, efficiency, and satisfaction, while the error component decreased.